Unusual paramagnet to ferromagnet phase transition and magnetic inhomogeneities in hole doped manganites - Lazuta, A.V.; Ryzhov, V.A.; Kiselev, I.A.; Chernenkov, Yu.P.; Smirnov, O.P.; Molkanov, P.L.; Troyanchuk, I.O.; Khomchenko, V.A. (Functional Materials, 2008)
Results of structural neutron diffraction study, nonlinear magnetic response and magnetic resonance measurements are presented for insulating La₀.₈₈MnO₂.₉₁ with Tc ≈ 216 K. The diffraction data are considered using the monoclinic P2/a and orthorhombic Pbnm space groups in a temperature range 4-300 K. The compound has been found to have the monoclinic structure at 300 K and orthorhombic one at 4 K. In the intermediate temperature range, these t\vo phases coexist. According to the data on nonlinear response and magnetic resonance, this compound exhibits an unconventional paramagnetic (P) to ferromagnetic (F) phase transition. Below T* ≈ 247 K, the usual P phase is transformed into a mixed state which is characterized by the appearance of the F regions in the P matrix. The temperature evolution of this state is very close to that found in the traditionally doped Nd₁₋ₓBaₓMnO₃ (x = 0.23, 0.25) manganites. This supports the supposition on universal character of this phenomenon, namely, formation of an inhomogeneous magnetic state above Tc with the coexistence of the P and F regions. The F domains are expected to exhibit a metallic state while the P phase is an insulator.